GGE biplot analysis for grain yield of single cross maize hybrids under stress and non-stress conditions - Kuchanur, P.H.; Salimath, P.M.; Wali, M.C.; Hiremath, Channayya (The Indian Journal of Genetics and Plant Breeding, 2016)
In AMMI analysis environment main effect and genotype × location interaction were found significant. Significant differences in maize hybrids were observed for grain yield among the locations over the years both under stress and non-stress conditions. Among the four interaction principal component axes (IPCA) of GGE biplot, first two IPCA were significant explaining 75.89 % variation. Hybrid, KDMI-15 × NEI-9202-B was found superior among all the hybrids over checks over all the locations. Other hybrids viz., CM-111 × HYD SEL-15 and CI-4 × NEI-9202-B exhibited almost no interaction with the environments convincing the reliability of their performance. The hybrids viz., KDMI-15 × NEI-9208- B, CM-111 × HYD SEL-17, 900M, CML-446 × HYD SEL-4, CI-4 × HYD SEL-17, HYD SEL-7 × KDMI-15 and HYD SEL-15 × HYD SEL-17 were most responsive.